Pengaruh Corporate Social Responsibility dan Financial Stability Terhadap Kinerja Perusahaan yang Dimoderasi oleh Agresivitas Pajak - Mulyadi Mulyadi (Media Akuntansi Perpajakan, 2021)
This study aims to analyze the effect of corporate social responsibility and financial stability on company performance with tax aggressiveness as a moderating variable. The independent variables are corporate social responsibility and financial stability. The dependent variable is the company's performance and tax aggressiveness as a moderating variable. The research data was collected from the publication of the annual financial statements of manufacturing companies in the industrial sub-sector that have been listed on the IDX. Samples were selected according to the sample selection criteria. The sample selection used for this research is purposive sampling method. This method performs sample selection to focus on a particular goal. The period of the financial statements studied is 2015-2019. The results of this study indicate that financial stability and tax aggressiveness have a significant impact on company performance. Tax aggressiveness is able to moderate the effect of financial stability on company performance. Meanwhile, corporate social responsibility does not affect the company's performance.Keywords: company performance, financial stability, tax aggressiveness, corporate social responsibility